A Case of Sudden Death: Subarachnoid Hemorrhage, Pheochromocytoma, Berry Aneurysm - Ana B. Arevalo; Jacxelyn Moran; Stephen Zink; Binny Khandakar (Hindawi Limited, 2019)
Subarachnoid hemorrhage is a medical emergency. Berry aneurysm rupture is the second most common cause following trauma. Diagnosis is often challenging. Neurogenic heart syndrome often complicates subarachnoid hemorrhage. A concomitant pheochromocytoma can be deadly causing sudden cardiac arrhythmia. Here, we describe a case of subarachnoid hemorrhage with concomitant incidental pheochromocytoma in a relatively young female who died suddenly, diagnosed during autopsy. A 57-year-old Hispanic woman with past medical history of asthma, prediabetes, and uncontrolled hypertension collapsed unexpectedly. She initially had ventricular tachycardia, followed by pulseless electrical activity and finally asystole without response to resuscitation. In the emergency department she was on epinephrine, calcium, naloxone, and tPA with suspected thrombotic stroke. Despite measures, she was pronounced dead. Autopsy revealed subarachnoid hemorrhage due to a ruptured berry aneurysm. Additionally, pheochromocytoma was detected in the right adrenal gland. Subarachnoid hemorrhage has a grave prognosis by itself. This case describes the uncommon detection of pheochromocytoma in the setting of subarachnoid hemorrhage.